2020
DOI: 10.1371/journal.pone.0240218
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal modeling of visceral leishmaniasis in Midwest Brazil: An ecological study of 18-years data (2001–2018)

Abstract: Visceral leishmaniasis (VL) is a neglected vector-borne disease associated with socioeconomic and environmental issues. In Brazil, epidemics of VL have occurred in major cities since 1980. Applied models for medical and epidemiological research have been used to assess the distribution and characteristics of disease endpoints and identify and characterize potential risk factors. This study described the demographic features of VL and modeled the spatio-temporal distribution of human VL cases and their relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
4
2
0
Order By: Relevance
“…According to an epidemiological bulletin on VL in Mato Grosso do Sul between 2011 and July 2020, 1,741 cases were confirmed, with an annual average of 174.1 cases and 124 deaths (Bogiani & Oliveira, 2020). In the municipality of Campo Grande, Mato Grosso do Sul, from 2001 to 2018, 1,855 VL cases were reported, with an annual average of 103.0 cases and annual average incidence rate of 13.23 cases/100,000 inhabitants, demonstrating the rapid transition from epidemic to endemic (Oliveira et al, 2020). These data corroborate the present findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to an epidemiological bulletin on VL in Mato Grosso do Sul between 2011 and July 2020, 1,741 cases were confirmed, with an annual average of 174.1 cases and 124 deaths (Bogiani & Oliveira, 2020). In the municipality of Campo Grande, Mato Grosso do Sul, from 2001 to 2018, 1,855 VL cases were reported, with an annual average of 103.0 cases and annual average incidence rate of 13.23 cases/100,000 inhabitants, demonstrating the rapid transition from epidemic to endemic (Oliveira et al, 2020). These data corroborate the present findings.…”
Section: Discussionsupporting
confidence: 91%
“…With regard to sociodemographic aspects, according to the Epidemiological Bulletin on VL that was published in 2020, the most affected age group in the state of Mato Grosso do Sul was 35-49 years old (22.9%), followed by 1-4 years old (17.1%), most of whom were male (65.0%) (Bogiani & Oliveira, 2020). In Campo Grande, the most affected age groups were children up to 5 years old and adults over 40 years old, and the highest incidence was in males (Oliveira et al, 2020). In the present study, the most affected age groups in Mato Grosso do Sul and Corumbá were up to 5 years old and 20-59 years old, and the most affected were also male (p < 0.05).…”
Section: Discussionsupporting
confidence: 46%
“…The connection between socioeconomic status and risk of VL in Brazil is strongly supported by prior literature [22,45,46]. Mediating factors PLOS NEGLECTED TROPICAL DISEASES such as sanitation [47,48] and literacy [4,11] contribute to risk in the same direction as the present analysis.…”
Section: Discussionsupporting
confidence: 89%
“…Human visceral leishmaniasis (VL) is endemic in Brazil [1][2][3][4][5][6][7][8][9][10][11][12] and is recognized as a neglected tropical disease by the World Health Organization [13]. In Brazil, VL etiology stems from the protozoan Leishmania infantum, where the domestic dog serves as a sentinel host with the phlebotomine sand fly as the typical vector [14].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have applied either spatial models or geostatistical models to determine the predictors of CL incidence. To our knowledge, only two studies in Brazil [ 26 ] and Ethiopia [ 27 ], have applied spatiotemporal models to identify the underlying risk factors of human VL incidence. The study in Brazil used GAM (generalized additive models) and showed that quality of life in an urban area (a composite index related to income, education, housing, and environmental sanitation) was inversely related to VL incidence.…”
Section: Introductionmentioning
confidence: 99%